The Effect of Backhand Groundstroke Training Variations on Backhand Ability in the Unimed Court Tennis Community in 2022 - Ronaldo Abadi S. Kembaren; Irwansyah Siregar (Journal of Indonesian Active in Sports, 2024)
This study aims to determine the effect of backhand groundstroke training variations on backhand ability in the Unimed tennis community in 2022. This research was conducted on the Unimed tennis court, Jalan William Iskandar Pasar V Medan Estate with a population of 20 students and a sample of 10 students. The research period was conducted from February 18th to April 3rd, 2022 with a frequency of 18 sessions for 6 weeks. This study used experiments with the test instrument in this study, namely the backhand ability test. The independent variable in this study is backhand groundstroke training and backhand ability is as the dependent variable. From the results of data processing with statistical analysis, it is obtained that tcount is equal to 4.56 and ttable is equal to 2.26 based on the distribution table of t with dk (n-1) 10 - 1 equal to 9 and at the Î± level of 0.05 equals to 2.26 which means tcount > ttable (4.56 > 2.26). Thus, Ha is accepted and H0 is rejected. In this case, it can be concluded that variation trainings in backhand groundstroke have a significant influence on the results of backhand ability in the Unimed court tennis community in 2022.